Development of an RGB LED panel controller system for smart traffic lights - Borsato Miskalo, Bruna; Fernando Pinto de Oliveira, Luiz; Luiz Rossini, Flavio; Denis Garcez da Luz, Paulo (Seven Editora, 2023)
This work reports the development of an electronic device to be applied in an urban traffic light system, capable of showing relevant information such as the remaining time of the signal and additional information from sensor data to control traffic, sharing information useful to drivers and pedestrians. Studies were carried out on the topic of smart traffic management, new strategies under development and improvement in recent years of research, and the consequences of traffic on urban roads, to propose the principle and parameters of the device’s operation, based on the system’s efficiency. Through studies, it was noted that the traditional traffic light system has its limitations, such as excessive expenses with light bulbs, and problems with electrical failures, in addition to the fact that congestion increases the emission of polluting gases and harms the health of drivers and pedestrians. In this sense, there is the possibility that an RGB LED panel controller offers useful and clear information, received by a device via UART communication so that it is possible to obtain a lower rate of traffic congestion. Soon, a micro-controlled LED panel management system will be developed to replace traditional traffic lights and focus groups. DOI: 10.56238/pacfdnsv1-110